Synthesis and characterization of reusable magnetic TiO2/chitosan/Fe3O4 nanocomposite for the photocatalytic degradation of ortho nitrophenol pollutant / Saba Afzal - Saba , Afzal (2019)
Designing a Titanium Oxide (TiO2) nanoparticles based catalyst with improved photocatalytic activity in visible region of light with efficient recycling ability is desirable. As TiO2 is one of the most attractive materials in nanotechnology due to its superior photo-catalytic oxidation ability, non-photo-corrosive and nontoxic nature. Despite of its excellent properties, the problems of rapid electron hole pair recombination, wide band gap and poor catalyst reusability narrows the applications of TiO2 nano particles. The present research aims to synthesize titanium dioxide-chitosan-magnetite (TiO2/CS/Fe3O4) nano composite with enhanced adsorption characteristics, minimize electron hole pair recombination of TiO2, improves activity in visible region of light and efficient recycling of catalyst after wastewater treatment. CS is an excellent adsorbent with functional groups (NH2, OH) which are responsible of adsorbing organic pollutants. It served as a linker between TiO2 and Fe3O4 to facilitate the overall photocatalysis. Recycling of TiO2 by using traditional methods produce secondary pollutants to the environment, however, separation techniques by applying magnetic adsorbent are an alternative way. Fe3O4 nano particles are useful in biological and environmental applications because of their large surface area, nano size dimension and strong response to external magnetic field. Thus, Fe3O4 give efficient separation of catalyst after wastewater treatment. Presence of Fe3O4 shows significant reduction in the band gap of TiO2 (from 3.19 eV to 2.85 eV) which shifts the photoactivity of composite in visible region. Fe3O4/CS core was synthesized by Co-precipitation as it is a simple and an economical method give well dispersed Fe3O4 nano particles with the success rate from 96 to 99.9%. Effect of concentration of each individual component (TiO2, CS and Fe3O4) on the physicochemical and photocatalytic properties of TiO2/CS/Fe3O4 (TCF) nancomposite has been studied. The effectiveness of the optimize TCF nanocomposite was then be assessed using ortho-nitrophenol (ONP) which is considered as the most toxic and persistent organic pollutant (POP) of industrial wastewater. By using 0.02 g of optimized TCF nanocomposite >90% degradation of ONP was achieved within 180 minutes in visible region. The percent photodegradation of ONP was studied by using UV-vis spectrophotometer while the degradation pathway of ONP was studied by using liquid chromatography mass spectroscopy (LC-MS). The superior photocatalytic performance of ternary system (TiO2/CS/Fe3O4) along with the advantage of easy recoverability could make it a new appealing catalyst for wastewater treatment applications.